2021
DOI: 10.21522/tijmg.2015.07.02.art010
|View full text |Cite
|
Sign up to set email alerts
|

Product Differentiation Strategy and Perceived Financial Performance of Commercial Banks in Uganda

Abstract: The banking landscape in Uganda is such that there is a section of commercial banks that has consistently posted impressive performance figures, particularly over the last five years, while the performance of the others leaves a lot to be desired. This study’s purpose was to examine the effect of differentiation strategy on the financial performance of commercial banks in Uganda. The study employed a cross-sectional design characterized by a quantitative approach. The target population in this study constitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(27 reference statements)
0
0
0
Order By: Relevance
“…Pieces of literature have shown that indeed differentiation is a good predictor of performance, regardless of the approach used; qualitative or quantitative. However, as the results are mixed, with both positive, mediation, and negative correlations, this implies that the differentiation-performance nexus is far from clear (Wambaka & Adegbuyi, 2021). Therefore, it is only further analysis by other studies, that can help in understanding and clarifying the debate.…”
Section: Empirical Review and Hypothesis Developmentmentioning
confidence: 95%
See 1 more Smart Citation
“…Pieces of literature have shown that indeed differentiation is a good predictor of performance, regardless of the approach used; qualitative or quantitative. However, as the results are mixed, with both positive, mediation, and negative correlations, this implies that the differentiation-performance nexus is far from clear (Wambaka & Adegbuyi, 2021). Therefore, it is only further analysis by other studies, that can help in understanding and clarifying the debate.…”
Section: Empirical Review and Hypothesis Developmentmentioning
confidence: 95%
“…For example, Wambaka and Adegbuyi (2021) explored product differentiation's impact on performance in the banking sector. A cross-sectional design (focusing on quantitative data) was adopted, where 144 chief executives and senior managers from 10 commercial banks participated in the study.…”
Section: Empirical Review and Hypothesis Developmentmentioning
confidence: 99%
“…Dengan melakukan diferensiasi produk, bisnis dapat menawarkan nilai tambah yang berbeda dan menarik bagi masing-masing segmen pasar. Secara umum teori diferensiasi produk menekankan pentingnya menciptakan keunikan pada produk atau jasa yang ditawarkan (Wambaka & Adegbuyi, 2021). Dalam pasar tradisional, pedagang tetap memiliki keunggulan dalam diferensiasi produk karena keberadaan lapak tetap mereka.…”
Section: Strategi Pemasaran Segmen Dan Diferensiasiunclassified
“…In the financial market, product differentiation involves the creation of unique financial products and services that set a financial institution apart from its competitors. Because of personalizing offerings to meet specific and specific customer needs and preferences, financial institutions can attract more customers, increase customer loyalty, and ultimately improve the quality of their services (Wambaka, 2021). Product differentiation allows financial institutions to offer a wide variety of products and services that go beyond traditional banking.…”
Section: Introductionmentioning
confidence: 99%